2022
DOI: 10.3390/ma15124309
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Road Performance of Asphalt Mixtures Based on Infrared Thermography

Abstract: Temperature segregation during the paving of asphalt pavements is one of the causes of asphalt pavement distress. Therefore, controlling the paving temperature is crucial in the construction of asphalt pavements. To quickly evaluate the road performance of asphalt mixtures during paving, in this work, we used unmanned aerial vehicle infrared thermal imaging technology to monitor the construction work. By analyzing the temperature distribution at the paving site, and conducting laboratory tests, the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The existing research also showed that the angular deviation of the tamper pairs in the vibrational screed system also affected the asphalt paver's working performance and pavement quality. [2][3][4][5][6][7][8][9][10]16 However, in this experiment, the effect of the angular deviation of the tamper pairs has been ignored. In order to ameliorate the asphalt paver's working performance, the maximum RMS a needs to be achieved and distributed evenly on the length of the vibrational screed system.…”
Section: Experiments With the Working Performance Of Asphalt Pavermentioning
confidence: 99%
See 1 more Smart Citation
“…The existing research also showed that the angular deviation of the tamper pairs in the vibrational screed system also affected the asphalt paver's working performance and pavement quality. [2][3][4][5][6][7][8][9][10]16 However, in this experiment, the effect of the angular deviation of the tamper pairs has been ignored. In order to ameliorate the asphalt paver's working performance, the maximum RMS a needs to be achieved and distributed evenly on the length of the vibrational screed system.…”
Section: Experiments With the Working Performance Of Asphalt Pavermentioning
confidence: 99%
“…Then, this model was also applied to assess the asphalt paver's pavement quality under the effect of the moving speed, mass, and excitation of the vibrational screed system. 4,[8][9][10] Research indicated that under the excitations of the vibrational screed system from 12 to 20 Hz, the asphalt paver's pavement quality was significantly ameliorated. This excitation with other parameters of the vibrational screed system including the eccentric distance and eccentric mass were then optimised to further enhance the pavement quality.…”
Section: Introductionmentioning
confidence: 99%
“…The uncontrollable temperature problem during the construction of asphalt pavement is one of the causes of asphalt pavement damage. Here is a report on the pavement performance and service life issues caused by temperature segregation during paving with asphalt pavement [ 12 ]. Through the use of unmanned aerial vehicle infrared thermal imaging technology to collect the temperature distribution of an asphalt mixture pavement construction site and by simulating on-site pavement conditions in the laboratory, it was concluded that the prediction results for the performance of asphalt mixture pavement obtained using unmanned aerial vehicle infrared thermal imaging technology have a high accuracy, and the relationship between the melt temperature, high-temperature stability and water stability of asphalt mixture was determined.…”
mentioning
confidence: 99%